STUDY OF RESISTANCE TO ATTACKS OF REPRODUCING REMOTE CONTROL PROTOCOLS USING THE 433 MHz RADIO CHANNEL - Mykhaylova, Olha; Artem, Stefankiv (Ukrainian Information Security Research Journal, 2024)
This article identifies critical vulnerabilities in the EV1527 protocol that are widely used in remote control systems, particularly home automation systems. Focusing on a detailed analysis of the protocol structure and potential weaknesses, this study assesses the risks of replay attacks that can be carried out by intercepting and retransmitting radio signals. The results of the work demonstrate the significant vulnerability of this protocol to such attacks due to the lack of cryptographic protection of the transmitted data. As part of this work, experimental tests were conducted using the HackRF One software-controlled transceiver, which allowed to reproduction of the attack in controlled laboratory conditions. The experiments confirmed theoretical assumptions about the possibility of implementing such attacks, emphasizing the need to develop more secure communication protocols. HackRF One's application demonstrated how easily attackers can intercept and rebroadcast signals, gaining unauthorized access to remote control systems. This article highlights the importance of transitioning from legacy technologies to modern solutions that include dynamic codes and cryptography to increase security. The use of dynamic codes, such as the HCS301's moving code technology, greatly complicates the possibility of replay attacks because each code transmission is unique. This means that even if the signal is intercepted, an attacker will not be able to repeat it to gain access. The authors recommend the implementation of cryptographic methods, such as the HCS301 moving code technology, which greatly complicates the possibility of repeated attacks. The introduction of such technologies increases the level of security and makes remote control systems more resistant to malicious actions. In addition, the need for constant updating and improvement of security protocols to protect critical infrastructure is emphasized. Given these results, this work indicates an urgent need for updating and improving remote control systems, including the development of new, more attack-resistant protocols, especially in the context of ensuring the security of critical infrastructure facilities. The integration of modern cryptographic methods is a key step to protect against malicious attacks and ensure the reliable operation of remote-control systems.